HSC70 Inhibits Spring Viremia of Carp Virus Replication by Inducing MARCH8-Mediated Lysosomal Degradation of G Protein - Li, Chen; Shi, Lin; Gao, Yan; Lu, Yuanan; Ye, Jing; Liu, Xueqin (Frontiers in Immunology, 2021)
As a fierce pathogen, spring viremia of carp virus (SVCV) can cause high mortality in the common carp, and its glycoprotein (G protein) is a component of the viral structure on the surface of virion, which is crucial in viral life cycle. This report adopted tandem affinity purification (TAP), mass spectrometry analysis (LC-MS/MS), immunoprecipitation, and confocal microscopy assays to identify Heat shock cognate protein 70 (HSC70) as an interaction partner of SVCV G protein. It was found that HSC70 overexpression dramatically inhibited SVCV replication, whereas its loss of functions elicited opposing effects on SVCV replication. Mechanistic studies indicate that HSC70 induces lysosomal degradation of ubiquitinated-SVCV G protein. This study further demonstrates that Membrane-associated RING-CH 8 (MARCH8), an E3 ubiquitin ligase, is critical for SVCV G protein ubiquitylation and leads to its lysosomal degradation. Furthermore, the MARCH8 mediated ubiquitylation of SVCV G protein required the participation of HSC70 through forming a multicomponent complex. Taken together, these results demonstrate that HSC70 serves as a scaffold for MARCH8 and SVCV G, which leads to the ubiquitylation and degradation of SVCV G protein and thus inhibits viral replication. These findings have established a novel host defense mechanism against SVCV.